Do Specific Classroom Reading Activities Predict English Language Learners' Later Reading Achievement?. Issue 3 (4th May 2017) - Swanson, H. Lee; Orosco, Michael J.; Kudo, Milagros Fatima
ABSTRACT: This study investigated the relationship between elementary classroom ( N  = 50) reading activities in Year 1 and reading performance (i.e., passage comprehension, letter-word identification, and word attack) 1 year later for English language learners (ELLs; N  = 270). A cross-classification hierarchical model indicated that compared to other reading activities, grammar and spelling activities yielded the highest effect sizes (beta weights) in predictions of English passage comprehension. The analyses also showed that vocabulary and structural analysis instruction yielded the highest effect sizes in predictions of English letter-word identification and word attack. We discuss the results in the context of specific instructional activities that were predictive of ELL children's later reading outcomes.